Pengaruh Lokasi Dan Fasilitas Terhadap Kepuasan Pelanggan di Café Mie Setang Kecamatan Rantepao Kabupaten Toraja Utara - Arif Ballang; Althon K. Pongtuluran; Randi Tangdialla (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study was to determine whether there is an influence of location and facilities on customer satisfaction at Café Mie Setang. data collection procedures from this study, namely: observation, questionnaires, and documentation. The data analysis technique is quantitative with multiple linear regression tests. The calculation results show that partially location (X1) has no effect on customer satisfaction (Y) at Café Mie Handlebars, this is shown from the acquisition of a tcount of 1.5000 and a ttable of 1.678, with a significance of 0.140 while facilities (X2) have an effect oncustomer satisfaction (Y) at Café Mie Setang, this is shown from the acquisition of a tcount of 6,619 and a ttable of 1.678, with a significance of 0.000. and simultaneously location (X1), and facilities (X2) affect customer satisfaction (Y) at Café Mie Handlebars. this is shown from the acquisition of Fcount 29,726 and Ftable 3.20 with a significant level of 0.000.